Principles of taxation for business and investment planning 1999 - Jones, Sally M. ([S.l.] : Mcgraw-Hill College, 1998)
This text seeks to force readers to recognize the roles taxes play in business and investment decisions. It also provides an overview of the general role of taxation and its implications across business and presents the details of specific exceptions.
Keywords: taxation